B-site high-entropy solid oxide electrolytic cell cathode material as well as preparation method and application thereof
By adopting the B-position high-entropy solid oxide electrolytic cell cathode material with A2B2O6 high-entropy perovskite structure, the stability and conductivity problems of existing SOEC cathode materials when used at high temperatures are solved, and the high current density and structural stability are improved.
Patent Information
- Application Number
- CN202411634388.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-15
AI Technical Summary
Existing solid oxide electrolytic cell (SOEC) cathode materials are prone to nickel agglomeration, redox instability, carbon deposits and sulfur poisoning when used at high temperatures, and the conductivity and fuel catalytic activity of perovskite structure oxides are low. , limiting its commercial applications.
The cathode material of B-position high-entropy solid oxide electrolytic cell with A2B2O6 type high-entropy perovskite structure is formed by mixing Sr elements with transition metal elements Fe, Ti, Cr, Mn, Mo, and Co in a specific molar ratio to form the An electron ion hybrid conductor that transports oxygen ions and electrons simultaneously.
Effectively reduce the polarization resistance of the cathode of the oxygen ion-conducting solid oxide electrolytic cell, improve the electrolytic current density of the electrolytic cell, and maintain good structural stability under a pure carbon dioxide atmosphere, thereby enhancing the output stability of the cell.
Smart Images

Figure CN119518005A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid oxide electrolytic cells, and in particular relates to a B-site high entropy solid oxide electrolytic cell cathode material and a preparation method and application thereof. Background Art
[0002] Among the existing CO2 conversion methods, electrochemical reduction of CO2 has the main advantages of adjustable output with applied voltage and the consumption and utilization of renewable energy. Under high temperature (>700℃) operating conditions, the use of solid oxide electrolysis cells (SOECs) for CO2 electrolysis has good thermodynamic efficiency and fast electrokinetic rate, thus achieving excellent current density and energy efficiency.
[0003] The electrode material of the cathode of SOEC has always been the electrode material of the anode of solid oxide fuel cell (SOFC). Traditional SOFC metal ceramic anodes such as Ni / YSZ are prone to nickel agglomeration, redox instability, carbon deposition and sulfur poisoning when using hydrocarbon fuels. Perovskite structured oxides have excellent anti-carbon deposition ability, strong impurity tolerance, high redox stability and high ionic and electronic conductivity. However, this type of material has the problem of low electrical conductivity and fuel catalytic activity, which brings great difficulties to its commercial application. The high entropy effect of high configuration entropy perovskite oxides in thermodynamics, lattice distortion effect in structure, slow diffusion effect in kinetics and "cocktail" effect in electrical properties make this type of material have great application prospects. Therefore, it is of great significance to develop high-performance SOEC cathode materials. Summary of the invention
[0004] The purpose of the present invention is to provide a B-site high entropy solid oxide electrolytic cell cathode material and its preparation method and application. The material can simultaneously transmit oxygen ions and electrons, can effectively reduce the polarization resistance of the cathode of the oxygen ion conductive solid oxide electrolytic cell, improve the electrolysis current density of the electrolytic cell, and can maintain good structural stability in a pure carbon dioxide atmosphere, effectively enhancing the output stability of the battery.
[0005] To achieve the above-mentioned purpose, the present invention provides a B-site high-entropy solid oxide electrolytic cell cathode material, the cathode material is an A2B2O6 type high-entropy perovskite structure, wherein the A-site element is Sr element, and the B-site element is composed of six transition metal elements Fe, Ti, Cr, Mn, Mo, and Co mixed in a molar ratio of 5:1:1:1:1:1.
[0006] As a further solution of the present invention: the chemical formula of A2B2O6 is Sr2FeTi 0.2 Cr 0.2 Mn 0.2 Mo0.2 Co 0.2 O6.
[0007] A method for preparing a cathode material for a B-site high entropy solid oxide electrolytic cell comprises the following steps:
[0008] S1, dissolving the precursors corresponding to the constituent elements of the cathode material of the solid oxide electrolytic cell in water according to a stoichiometric ratio to obtain a metal ion aqueous solution;
[0009] S2, adding a complexing agent to the metal ion aqueous solution obtained in step S1, and adjusting the pH value to obtain a complexing sol;
[0010] S3, heating and stirring the complex sol obtained in step S2 at 80° C. to evaporate to form a gel, followed by self-propagating combustion to obtain an initial powder;
[0011] S4, transferring the initial powder obtained in step S3 to a high temperature furnace for drying and calcining to obtain a B-site high entropy solid oxide electrolytic cell cathode material powder.
[0012] As a further solution of the present invention: in step S1, the precursors of the constituent elements Sr, Fe, Cr, Mn and Co are nitrates, the precursor of Ti is titanium dioxide, and the precursor of Mo is ammonium molybdate.
[0013] As a further solution of the present invention: the complexing agent in step S2 is one or two of citric acid and ethylenediaminetetraacetic acid, the ratio of the molar number of the complexing agent to the total molar number of metal ions is 1:1-3:1, and ammonia water is added to adjust the pH value to 7.
[0014] As a further solution of the present invention: in step S4, the drying is carried out in a high-temperature drying oven at a temperature of 300° C. for 10 hours, and the calcination is carried out in a muffle furnace at 1200° C. for 10 hours.
[0015] One application of the above-mentioned B-site high entropy solid oxide electrolyzer cathode material is to be applied to the cathode of a solid oxide fuel cell.
[0016] Compared with the prior art, the present invention dopes transition metal elements Fe, Ti, Cr, Mn, Mo, and Co at the B position. The cathode material is an electron ion mixed conductor with good electrical conductivity. In addition, the ion radii of the above six B-position elements are close, and the difference in ion size is small, which is conducive to forming a stable single-phase structure. 0.2 Cr 0.2 Mn 0.2 Mo 0.2 Co 0.2O6 high entropy perovskite material can transmit oxygen ions and electrons at the same time, which can effectively reduce the polarization resistance of the cathode of oxygen ion conductive solid oxide electrolyzer, improve the electrolysis current density of the electrolyzer, and maintain good structural stability in a pure carbon dioxide atmosphere, which can effectively enhance the output stability of the battery. Its preparation method is simple and can be applied to solid oxide fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the XRD pattern of SFTCMMC high entropy perovskite material synthesized by sol-gel method.
[0018] Figure 2 This is the XRD diagram of the high entropy perovskite material SFTCMMC after reduction in CO2 atmosphere.
[0019] Figure 3 It is the IV diagram of the SOEC assembled in the embodiment under different temperature conditions for the electrolysis of CO2.
[0020] Figure 4 It is the EIS graph of the SOEC assembled in the embodiment under different temperature conditions for the electrolysis of CO2. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with the accompanying drawings.
[0022] A B-site high entropy solid oxide electrolytic cell cathode material is an A2B2O6 type high entropy perovskite structure, wherein the A-site element is Sr, and the B-site element is a mixture of six transition metal elements Fe, Ti, Cr, Mn, Mo, and Co in a molar ratio of 5:1:1:1:1:1. The cathode material is an electron-ion mixed conductor with good electrical conductivity. The ion radii of the above six B-site elements are close, and the difference in ion size is small, which is conducive to forming a stable single-phase structure. The specific chemical formula is: Sr2FeTi 0.2 Cr 0.2 Mn 0.2 Mo 0.2 Co 0.2 O6.
[0023] A method for preparing a cathode material for a B-site high entropy solid oxide electrolytic cell comprises the following steps:
[0024] S1, dissolving the precursors corresponding to the constituent elements of the cathode material of the solid oxide electrolytic cell in water according to a stoichiometric ratio to obtain a metal ion aqueous solution;
[0025] S2, adding a complexing agent to the metal ion aqueous solution obtained in step S1, and adjusting the pH value to obtain a complexing sol;
[0026] S3, heating and stirring the complex sol obtained in step S2 at 80° C. to evaporate to form a gel, followed by self-propagating combustion to obtain an initial powder;
[0027] S4, transferring the initial powder obtained in step S3 to a high temperature furnace for drying and calcining to obtain a B-site high entropy solid oxide electrolytic cell cathode material powder.
[0028] Wherein, in step S1, the precursors of the constituent elements Sr, Fe, Cr, Mn and Co are nitrates, the precursor of Ti is titanium dioxide, and the precursor of Mo is ammonium molybdate.
[0029] The complexing agent in step S2 is one or more of citric acid, ethylenediaminetetraacetic acid, and glycine, the ratio of the molar number of the complexing agent to the total molar number of metal ions is 1:1-3:1, and ammonia water is added to adjust the pH value to 7.
[0030] In step S4, drying is performed in a high-temperature drying oven at a temperature of 300° C. for 10 h, and calcination is performed in a muffle furnace at 1200° C. for 10 h.
[0031] The purpose of drying is to remove ammonia in nitrate and moisture in raw materials to prevent pores and cracks from appearing during the later sintering process, and to obtain crystallized precursor powder.
[0032] The purpose of calcination is to remove organic matter and increase density, and to refine the grains under high temperature to obtain high-entropy perovskite ceramic materials with regular grain shape and size.
[0033] An application of the B-site high entropy solid oxide fuel cell cathode material as described above is used for the cathode of a solid oxide cell. The preparation method of the solid oxide cell is as follows:
[0034] A, mixing the above-mentioned B-position high entropy solid oxide fuel cell cathode material powder with a binder, transferring the mixture into a ball mill and mixing them evenly to obtain a cathode slurry;
[0035] B. The cathode slurry is evenly coated on the surface of the barrier layer by screen printing or brushing, and sintered at 1000-1200° C. for 1-3 hours to obtain a solid oxide battery cathode.
[0036] In step A, the applicable electrolyte is scandium stabilized zirconia or lanthanum strontium gallium magnesium. The binder is one or more of terpineol, ethyl cellulose, dibutyl phthalate, and butyl carbitol, and the mass fraction of ethyl cellulose is 3-7wt%.
[0037] In the step b, the barrier layer slurry is gadolinium-doped cerium oxide or samarium-doped cerium oxide.
[0038] Example:
[0039] Sr2FeTi 0.2 Cr 0.2 Mn 0.2 Mo 0.2 Co 0.2 Preparation of O6 high entropy perovskite materials
[0040] S1, according to the chemical formula Sr2FeTi 0.2 Cr 0.2 Mn 0.2 Mo 0.2 Co 0.2 O6, weigh Sr(NO3)2, Fe(NO3)3·9H2O, TiO2, Cr(NO3)3·9H2O, H8MnN2O according to the stoichiometric ratio. 10 、(NH4)6Mo7O 24 ·4H2O, Co(NO3)2·6H2O are dissolved in 300ml of deionized water in sequence. After the nitrate is completely dissolved, a complexing agent is added, which includes citric acid and ethylenediaminetetraacetic acid. Citric acid is added and stirred to dissolve at a molar ratio of total metal ions to citric acid of 1:1, and ethylenediaminetetraacetic acid is added to the solution at a ratio of 1.5:1 to total metal ions, and ammonia water is added to adjust the pH value to 7 to obtain a complexing solution.
[0041] S2, heating the complex sol obtained in step S1 on a heating table at 80° C. to evaporate and form a gel, followed by self-propagating combustion to obtain an initial powder;
[0042] S3, transferring the primary powder obtained in step S2 to a high-temperature drying oven and drying it at 300° C. for 10 hours to obtain a crystallized precursor powder.
[0043] S4, putting the powder obtained in step S3 into a crucible and transferring it to a high temperature furnace for drying and calcining, heating the temperature to 1200°C at a heating rate of 2°C / min, keeping the temperature at 1200°C for 10 hours, and then cooling the temperature to room temperature at a cooling rate of 3°C / min to obtain the electrode material powder, and performing XRD analysis on the obtained powder. The results are as follows: Figure 1 shown.
[0044] S5, taking out the electrode material powder calcined in step S4 and placing it in a test furnace, calcining it at 850°C for 10 hours in a carbon dioxide atmosphere. The powder reduced in a carbon dioxide atmosphere is subjected to XRD analysis. The results are as follows: Figure 2 shown.
[0045] Depend on Figure 1-2It can be seen that the SFTCMMC fuel electrode material can be successfully prepared by the sol-gel method, and the material has a uniform single-phase perovskite structure. The powder can maintain a good perovskite structure after reduction in a carbon dioxide atmosphere, and no other impurity peaks appear, indicating that the fuel electrode material does not decompose in a carbon dioxide atmosphere and has good stability.
[0046] Application Example: Preparation Method of Solid Oxide Electrolytic Cell
[0047] A, weigh an appropriate amount of the above Sr2FeTi 0.2 Cr 0.2 Mn 0.2 Mo 0.2 Co 0.2 The O6 solid oxide battery fuel electrode powder material is placed in a mortar, and then an appropriate amount of binder (the binder is pine alcohol and ethyl cellulose), a plasticizer (dibutyl phthalate) and a dispersant (butyl carbitol) are added and ground evenly to obtain a fuel electrode slurry.
[0048] B, then weigh an appropriate amount of La 0.6 Sr 0.4 Co 0.2 Fe 0.8 o 3-δ and Ce 0.9 G 0.1 O 2-δ The powders were placed in a mortar at a mass ratio of 6:4, an appropriate amount of binder was added, and the mixture was mixed evenly to obtain the LSGF-GDC air electrode composite material.
[0049] C, and then weigh an appropriate amount of Ce 0.9 G 0.1 O 2-δ The barrier layer powder is put into a mortar, a certain amount of binder is added and ground evenly to form a barrier layer slurry;
[0050] D. The barrier layer slurry in step B is evenly coated on a 0.3 mm thick (Sc2O3) by screen printing. 0.1 (CeO2) 0.01 (ZrO2) 0.89 Both sides of the electrolyte were placed in an oven and dried for 30 minutes. The electrolytes were prepared by tape casting. The blanks were placed in an oven and dried for 10 hours, and then transferred to a muffle furnace and sintered at 1450°C for 3 hours.
[0051] E. The dried electrolyte is placed in a muffle furnace and sintered at 1250° C. for 3 h to obtain a multilayer electrolyte material.
[0052] F, the fuel electrode slurry and the air electrode composite material prepared in steps A and B are uniformly coated on both sides of the above-mentioned multilayer electrolyte material, and after drying, a full battery sheet is obtained, which is transferred to a high-temperature sintering furnace for sintering to obtain a Sr2FeTi 0.2 Cr 0. 2Mn 0.2 Mo 0.2 Co 0.2 Solid oxide electrolysis cell with O6 as cathode material, in which the fuel electrode material is Sr2FeTi 0.2 Cr 0.2 Mn 0.2 Mo 0.2 Co 0.2 O6 was sintered at 1100°C for 2 h in a high-temperature sintering furnace, and the air electrode material LSGF-GDC was sintered at 1050°C for 3 h in a high-temperature sintering furnace.
[0053] The solid oxide electrolytic cell prepared in step F was collected with silver palladium paste and silver wire, and then the single cell was sealed at one end of the ceramic tube with ceramic glue, with the fuel electrode facing inward, and fixed in the test furnace. The fuel electrode and air electrode of the electrolytic cell were connected to the electrochemical workstation through silver wire. During the SOEC performance test of the prepared electrolytic cell (SFTCMMC|GDC|SSZ|GDC|LSCF-GDC), the atmosphere on the fuel electrode side was controlled to be carbon dioxide, and the atmosphere on the air electrode side was controlled to be air. Figure 3 The IV curve of the electrolytic cell at 700℃-800℃ with different applied voltages. Under an applied voltage of 1.5V, the electrolysis current density of the single cell at 800℃, 750℃, and 700℃ is 0.76Acm -2 , 0.35Acm -2 , 0.19Acm -2 .
[0054] In order to further understand the electrochemical performance of the battery, electrochemical impedance spectroscopy was performed under an applied voltage of 1.5 V. Figure 4 As shown, the Rp at 700℃, 750℃, and 850℃ are 5.64Ωcm respectively. -2 , 2.17Ωcm -2 , 1.55Ωcm -2 .
Claims
1. A B-site high entropy solid oxide electrolytic cell cathode material, characterized in that: The cathode material is an A2B2O6 type high entropy perovskite structure, in which the A-site element is Sr, and the B-site element is composed of six transition metal elements Fe, Ti, Cr, Mn, Mo, and Co mixed in a molar ratio of 5:1:1:1:1:
1.
2. A B-site high entropy solid oxide electrolytic cell cathode material according to claim 1, characterized in that: The chemical formula of A2B2O6 is Sr2FeTi 0.2 Cr 0.2 Mn 0.2 Mo 0.2 Co 0.2 O6.
3. The method for preparing a B-site high entropy solid oxide electrolytic cell cathode material according to claim 1 or 2, characterized in that: The following steps are involved: S1, dissolving the precursors corresponding to the constituent elements of the cathode material of the solid oxide electrolytic cell in water according to a stoichiometric ratio to obtain a metal ion aqueous solution; S2, adding a complexing agent to the metal ion aqueous solution obtained in step S1, and adjusting the pH value to obtain a complexing sol; S3, heating and stirring the complex sol obtained in step S2 at 80° C. to evaporate to form a gel, followed by self-propagating combustion to obtain an initial powder; S4, transferring the initial powder obtained in step S3 to a high temperature furnace for drying and calcining to obtain a B-site high entropy solid oxide electrolytic cell cathode material powder.
4. The preparation method according to claim 3, characterized in that: In the step S1, the precursors of the constituent elements Sr, Fe, Cr, Mn and Co are nitrates, the precursor of Ti is titanium dioxide, and the precursor of Mo is ammonium molybdate.
5. The preparation method according to claim 3, characterized in that: The complexing agent in step S2 is one or both of citric acid and ethylenediaminetetraacetic acid, the ratio of the molar number of the complexing agent to the total molar number of metal ions is 1:1-1.5:1, and ammonia water is added to adjust the pH value to 7.
6. The preparation method according to claim 3, characterized in that: In step S4, the drying is carried out in a high temperature drying oven at a temperature of 300° C. for 10 hours, and the calcination is carried out in a muffle furnace at 1200° C. for 10 hours.
7. An application of the B-site high entropy solid oxide electrolytic cell cathode material as claimed in claim 1 or 2, characterized in that: Applied to solid oxide fuel cell cathode.
Citation Information
Patent Citations
High-entropy double-perovskite structure IT-SOFC cathode and preparation method thereof
CN118507739A
Cited By
High-entropy double-perovskite type direct ammonia solid oxide fuel cell anode material as well as preparation method and application thereof
CN120136537A